Om den i Aaret 1831 paa nogle Steder i Sjælland udbrudte Koppesyge blandt Faar. - Hald, J. C. (Tidsskrift for Landøkonomi, 2018)
Om den i Aaret 1831 paa nogle Steder i Sjælland udbrudte Koppesyge blandt Faar.